The Influence of Sports Game Teaching on the Cultivation of Talents in Innovation and Entrepreneurship Education - Fengjin Zhou, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
Objective: In order to understand the impact of innovation and entrepreneurship education talent cultivation, the author proposes a study on the impact of sports game teaching on innovation and entrepreneurship education talent cultivation.The research object is the current situation of innovation and entrepreneurship among undergraduate students in a sports college of a certain university. Taking undergraduate students at the College of Physical Education of the University in 2019, 2020 and 2021 as the survey objects, sports games were carried out. A random questionnaire survey was conducted on some undergraduate students in 2019, 2020, and 2021 levels of the University's School of Physical Education. 242 questionnaires were collected and 250 were distributed, with a 97.67% recovery rate. According to the findings, students attending sports colleges recognize the necessity of innovation and entrepreneurship education but have a limited grasp of its value, as well as insufficient courses and structured training for innovation and entrepreneurship. It is critical to help sports college students fully comprehend the relevant national policies that encourage college students to innovate and entrepreneurship in order to provide them with solid knowledge, skills, and practical foundation for future employment or innovation and entrepreneurship.